Strategies for the Effective Implementation of Information and Communication Technology (ICT) in Colleges of Education, Enugu State - Ibrahim, Tanimu Adam; Obinna, Joseph Okparaugo (CV. Media Inti Teknologi, 2024)
The purpose of this was to identify the effective strategies for implementing Information and Communication Technology (ICT) in Enugu State Colleges of Education. It assessed ICT implementation strategies in three colleges of education in Enugu State, concentrating on their scope, gender disparities, and techniques used across federal, state, and private colleges in the state. The study aimed to identify research variables based on behaviorist, cognitivist, and constructivist theories and their application in ICT and teacher education. The target population consisted of 2,500 100-level pre-service teachers from the three colleges of education. A proportionate stratified random sampling technique was used to select the sample from the three colleges of education in the state. 125 pre-service teachers participated in the study. The study used a descriptive survey research design, and pilot testing was conducted to ensure the validity and reliability of the questionnaire. The data were analyzed using both descriptive and inferential statistics using the Statistical Package for Social Scientists (SPSS). The results showed that ICT implementation in colleges of education is not fully utilized, resulting in low educational objectives. Based on the findings, it is recommended that the government, curriculum planners, in-service and pre-service teachers, and educational institutions be more proactive in adopting strategies that enhance the effective implementation of ICT in colleges of education.